(untitled) (Scientific journal of the Fergana State University, 2023)
The historical approach to the study of irrigating, new innovation ways and wasting of water has been revealed in the article, which is one of the burning issues. Therefore the theme of the research is considered to be actual nowadays. The reasons of ineffectiveness of irrigating are enlightened. It is proved that new modern ways of the drip irrigation give the better results in condition of Uzbekistan.